Medical education reform: a catalyst for strengthening the health system - Sanaee, Layli (Revue canadienne de l'éducation médicale, 2019)
Key points: Medical education reform of Canadian specialist doctors presents a unique opportunity for designing parallel health systems interventions. Applying a Health System Framework reveals wider implications of Competence by Design (CBD) and provides impetus for health system strengthening. CBD implications may include staffing shortages in academic hospitals, annual variation in medical education financing needs, new roles for clinician teachers, and greater demand for human health resource surveillance and patient outcome monitoring and analysis. Each implication provides an opportunity to strengthen Governance and Leadership processes, namely by increasing coordination, harmonization, and system responsiveness.